2020
DOI: 10.1111/ecog.05166
|View full text |Cite
|
Sign up to set email alerts
|

30% land conservation and climate action reduces tropical extinction risk by more than 50%

Abstract: Limiting climate change to less than 2°C is the focus of international policy under the climate convention (UNFCCC), and is essential to preventing extinctions, a focus of the Convention on Biological Diversity (CBD). The post‐2020 biodiversity framework drafted by the CBD proposes conserving 30% of both land and oceans by 2030. However, the combined impact on extinction risk of species from limiting climate change and increasing the extent of protected and conserved areas has not been assessed. Here we create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 60 publications
5
74
0
4
Order By: Relevance
“…A recent study modelling 289 219 species indicates that preserving 30% of terrestrial ecosystems can reduce extinction risk by more than 50% (Hannah et al . 2020). Yet, extinction risk decreases with increasing area conserved (Hannah et al .…”
Section: How Much Forest Needs To Be Maintained In a Landscape?mentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study modelling 289 219 species indicates that preserving 30% of terrestrial ecosystems can reduce extinction risk by more than 50% (Hannah et al . 2020). Yet, extinction risk decreases with increasing area conserved (Hannah et al .…”
Section: How Much Forest Needs To Be Maintained In a Landscape?mentioning
confidence: 99%
“…Yet, extinction risk decreases with increasing area conserved (Hannah et al . 2020). Furthermore, density estimates and population viability analyses are inherently uncertain (Pe’er et al .…”
Section: How Much Forest Needs To Be Maintained In a Landscape?mentioning
confidence: 99%
See 2 more Smart Citations
“…Many protected areas are under pressure by increasing human population and land use intensities in neighbouring buffer zones, or by changes in their protection status (Symes, Rao, Mascia, & Carrasco, 2016). Hannah et al (2020) showed that species extinction risk in the tropics could be halved if 30% of the land surface height, determine habitat suitability for animals (Smit & Prins, 2015;Tews et al, 2004) and link different trophic levels via biotic interaction networks (Schleuning et al, 2016;Walther, 2010). Vegetation structure and canopy characteristics also influence the near-surface microclimatic conditions, as well as albedo, surface roughness and partitioning of energy into sensible and latent heat fluxes (Bonan, 2008;Ozanne et al, 2003).…”
Section: Introductionmentioning
confidence: 99%